Laparoscopic removal of migratory intrauterine contraceptive device to the bladder : A Case report and literature review - Yennie Ayu Setianingsih; Wahjoe Djatisoesanto; Johan Renaldo (Radiology Case Reports, 2024)
The intrauterine contraceptive device (IUCD) is the most frequently used method of reversible contraception with high efficacy. Despite these benefits, rare complications, such as spontaneous migration of the device into adjacent organs, particularly the bladder, are possible. Minimally invasive surgery is a safe and effective procedure with few complications for the management of migrated IUCDs. We presented a 36-year-old multiparous woman referred by her gynecologist who had an IUCD inserted 4 years prior. She had been experiencing dysuria and lower abdomen pain for 3 months. Ultrasonography of the abdomen revealed a hyperechoic lesion on the bladder wall's left anterior-superior portion. An MRI revealed that the device was embedded in the bladder's anterior left wall. Under general anesthesia, a cystoscopy and laparoscopy exploration were subsequently scheduled. Cystoscopy was performed, but the long limb of the IUCD was embedded in the mucosal and muscular layers, preventing its removal from the bladder wall. Laparoscopic retrieval of the IUCD was performed without complications. The patient was discharged 2 days after surgery with a Foley catheter inserted in the bladder for 10 days. When the urethral catheter was removed, a cystoscopy was performed to confirm bladder wall healing. In the postoperative follow-up 1 month after IUCD removal, no abnormalities were observed. Patients with a suspected IUCD migration must undergo a comprehensive evaluation, regardless of whether they are symptomatic or asymptomatic. Before surgical retrieval, imaging such as ultrasonography and MRI were utilized to locate the migrated IUCD and consider therapeutic options. Even though cystoscopy is considered as an effective and safe minimally invasive procedure for managing a migrated IUCD to the bladder, laparoscopic removal could serve as an option once cystoscopy retrieval is failed.